Accelerated traffic replay method based on time compression - Shuo WANG; Jun BAI; Bailing WANG; Xu ZHANG; Hongri LIU (网络与信息安全学报)
With the proliferation of network traffic, replaying traffic in a virtual environment faces many problems.In order to meet the requirements of traffic integrity and accuracy in the replay process, an accelerated traffic replay method based on time-compressed was proposed to achieve accelerated replay of real network traffic in a virtual environment.The method prioritized the compression of the largest time interval in the set of time intervals, and reduced the compression of the smaller intervals, thus reducing the traffic spike per unit time caused by time compression, and reducing the packet loss rate of traffic.The effect was measured in terms of packet loss rate, time interval error and similarity.The experiments show that this method has a lower packet loss rate and lower time interval error compared with the isometric compression method, although it performs worse in similarity.